Is It Time to Reconsider the 60 Seconds- Diabetic Foot Screen Reorganizing the 60 Second Foot Exam for People with Diabetes? - Badriya Al-Lenjawi; Hashim Mohamed; Azzam Azmy (Dermatology, 2017)
Diabetic patients have 25% lifetime risk of developing foot ulceration. More than half of these ulcers may eventually become infected, which greatly increases the likelihood of subsequent amputations. Although a multidisciplinary approach is the standard management for treating diabetic foot ulcers (DFUs), screening of diabetic foot ulcers is an integral part of that process. This review highlights the importance of the Inow’s 60 seconds screening tool but at the same time highlights serious gaps in the screening tool which is supposed to be a comprehensive screening tool for use in diabetic patients. The authors have addressed these gaps in a constructive and scientific way thereby solidifying the screening tool further in order to capture all the features and complications of the diabetic foot.